Peculiarities in water use and supply of differentecological plant groups - N. A. Muromtsev; N. A. Semenov; K. B. Anisimov (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
Every ecological group of plants including hygrophytes, mesophytes and xerophytes is characterized by a definite narrow interval of the soil water potential, in which the values of relative transpiration cannot be lower than the optimal level (1.0-0.9). These intervals take into account the influence of soil properties (moisture potential) and meteorological conditions (transpiration) and can be used as optimal indices for the water supply of plants. The peculiar soil water uptake by plants has been studied to show that the soil water and its intensive uptake become increasing but its “dead” reserve decreasing from hygrophytes towards mesophytes and then xerophytes. It is worth emphasizing that the decline in the growth and accumulation of useful products by plants occur due to decreasing the content of soil water to the lower boundary of optimal moistening. The further decrease in soil moisture leads to permanent and then ultimate wilting of plants. Under study were also intervals for soil water potential corresponding to the moisture of ultimate wilting of different ecological plant groups. Lettuce (hygrophyte) is becoming dead when the content of soil water is equal to 1.5, oat (mezophyte) - 1.0 and xerophytes - lower than 1.0 of the wilting moisture. The method of “vegetative miniatures” widely adopted now is imperfect and can be performed only for preliminary notions about the lower limit for plant availability of the soil water.